QCD glueball sum rules and vacuum topology - Forkel, Hilmar [UNESP] (World Scientific Publishing, 2007)
Several key problems of QCD sum rules in the spin-0 glueball channels are resolved by implementing nonperturbative short-distance physics from direct instantons and topological charge screening. A lattice-based instanton size distribution and the IR renormalization of the nonperturbative Wilson coeffcients are also introduced. Results of a comprehensive quantitative sum rule analysis are reviewed and their implications discussed.